Multiple mechanisms are implicated in the generation of 5q35 microdeletions in Sotos syndrome. Issue 4 (1st April 2005) - Tatton-Brown, K; Douglas, J; Coleman, K; Baujat, G; Chandler, K; Clarke, A; Collins, A; Davies, S; Faravelli, F; Firth, H; Garrett, C; Hughes, H; et al.
Abstract : Background: Sotos syndrome (MIM 117550) is characterised by learning difficulties, overgrowth, and a typical facial appearance. Microdeletions at 5q35.3, encompassing NSD1, are responsible for ∼10% of non-Japanese cases of Sotos. In contrast, a recurrent ∼2 Mb microdeletion has been reported as responsible for ∼50% of Japanese cases of Sotos. Methods: We screened 471 cases for NSD1 mutations and deletions and identified 23 with 5q35 microdeletions. We investigated the deletion size, parent of origin, and mechanism of generation in these and a further 10 cases identified from published reports. We used "in silico" analyses to investigate whether repetitive elements that could generate microdeletions flank NSD1 . Results: Three repetitive elements flanking NSD1, designated REPcen, REPmid, and REPtel, were identified. Up to 18 cases may have the same sized deletion, but at least eight unique deletion sizes were identified, ranging from 0.4 to 5 Mb. In most instances, the microdeletion arose through interchromosomal rearrangements of the paternally inherited chromosome. Conclusions: Frequency, size, and mechanism of generation of 5q35 microdeletions differ between Japanese and non-Japanese cases of Sotos. Our microdeletions were identified from a large case series with a broad range of phenotypes, suggesting that sample selection variability is unlikely as a sole explanation for these differences and that variation in genomic architecture might be a contributory factor. Non-allelic homologous recombination between REPcen and REPtel may have generated up to 18 microdeletion cases in our series. However, at least 15 cannot be mediated by these repeats, including at least seven deletions of different sizes, implicating multiple mechanisms in the generation of 5q35 microdeletions.